2017
DOI: 10.1111/andr.12429
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sperm DNA quality in men presenting with testicular cancer and lymphoma using alkaline and neutral Comet assays

Abstract: Despite more cancers in young men over the past two decades, improvements in therapies give a greater chance to live full lives following treatment. Sperm genomic quality is variable following cancer diagnosis, so its assessment is important if sperm cryopreservation is being considered. Here, we evaluated DNA damage using two DNA damage assays: an alkaline and for the first time, a neutral Comet assays in men presenting with testicular cancer (n = 19 for alkaline and 13 for neutral group) and lymphoma (n = 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Genitourinary infections and subsequent leukocytospermia increases ROS production, increasing SDF [47][48][49][50][51]. Increase in SDF has also been reported in men with testicular cancer and other malignancies, which is suggested to be secondary to the associated endocrine alterations or OS in these pathologies [52][53][54][55].…”
Section: Clinical and Environmental Risk Factors Of Sperm Dna Fragmenmentioning
confidence: 99%
“…Genitourinary infections and subsequent leukocytospermia increases ROS production, increasing SDF [47][48][49][50][51]. Increase in SDF has also been reported in men with testicular cancer and other malignancies, which is suggested to be secondary to the associated endocrine alterations or OS in these pathologies [52][53][54][55].…”
Section: Clinical and Environmental Risk Factors Of Sperm Dna Fragmenmentioning
confidence: 99%
“…The analysis is performed using a fluorescence microscope with imaging software. This test can be performed in both alkaline and neutral conditions: alkaline Comet reveals both SSBs and DSBs in sperm DNA, while neutral Comet is capable of selectively detect DSBs ( 104 ). The Comet assay has been used for both the in vitro evaluation of the mutagenic activity of various chemicals on sperm ( 105 ) and in preliminary studies of the correlation between fertility and basal sperm DNA damage ( 106 ).…”
Section: Chromatin Integrity Evaluationmentioning
confidence: 99%
“…The authors found impaired semen parameters (sperm concentration, normal forms, and motility), an elevated FSH serum concentration and elevated sperm DNA damage in the TC patients in comparison with the control group of healthy volunteers. More recently, Kumar et al detected increased sperm DNA damage in 19 testicular cancers patients vs. 20 semen donors with both alkaline and neutral COMET, with higher levels of sperm DNA fragmentation in TC patients with abnormal semen parameters ( 104 ). In particular, under neutral conditions, the Authors reported a significant difference in DNA DSBs in men presenting with testicular cancer compared to fertile donors.…”
Section: Sperm Dna Damage In Testicular Cancermentioning
confidence: 99%
“…However, researchers have not reached a firm consensus regarding the impact of cryopreservation on sperm DNA integrity (Di Santo et al ., ). The controversy in the literature could be due to differences in sample size, semen quality, cryopreservation method and tests used to evaluate DNA integrity (Isachenko et al ., ; Paasch et al ., ; Valcarce et al ., ,b; Kumar et al ., ).…”
Section: Introductionmentioning
confidence: 97%